Concepts of Urban-Environmental History. - (:unkn) unknown (transcript, 2020)
In history, cities and nature are often treated as two separate fields of research. "Concepts of Urban-Environmental History" aims to bridge this gap. The contributions to this volume survey major concepts and key issues which have shaped recent debates in the field. They address unresolved questions and future challenges. As a handbook, the collection offers a comprehensive overview for researchers and students, both from a historical and an interdisciplinary background.
Keywords: Stadtökologie; Stadtumwelt; Stadtnatur; Stadtgeschichte; Stadtentwicklung; Umweltgeschichte